2010
DOI: 10.1002/cvde.200906801
|View full text |Cite
|
Sign up to set email alerts
|

The Growth of One‐Dimensional Single‐Crystalline AlN Nanostructures by HVPE and Their Field Emission Properties

Abstract: Single-crystalline AlN nanostructures, such as thin films, nanoneedles, nanocolumns, and nanowires, depending on the controlled gas-flow ratio, are synthesized by halide vapor-phase epitaxy (HVPE). In comparison with a typical vapor/ liquid/solid (VLS) mechanism for the growth of nanowires, well-aligned AlN nanorod arrays with diameters below 20 nm are grown on a catalyst-free Si substrate though a vapor/solid (VS) mechanism. Their structural and optical properties are measured by X-ray diffraction (XRD), tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The as-prepared AlN sample had a low turn-on field of 3.8 Vμm-1 and an intensive light emission at 519nm. Y. K. Byeun et al [11] reported the controlled growth by HVPE of one dimensional single-crystalline AlN nanostructure arrays by employing various controlled growth conditions, such as growth temperature, gas flow rate, and the effects of the use or non-use of catalysts, and they also investigated the field emission properties of these single-crystalline AlN nanostructures, the results showed that the as-grown AlN nanostructures had a low turn-on field and threshold field of 2.25 and 3.58Vmm-1, respectively. However, the randomly distributed AlN nanostructure is not suitable for the final FED anode due to the screening effect, only the highly ordered and orientated AlN nanoarray is the key for production even emission, high lightening, low loss and addressable FED devices.…”
Section: Introductionmentioning
confidence: 99%
“…The as-prepared AlN sample had a low turn-on field of 3.8 Vμm-1 and an intensive light emission at 519nm. Y. K. Byeun et al [11] reported the controlled growth by HVPE of one dimensional single-crystalline AlN nanostructure arrays by employing various controlled growth conditions, such as growth temperature, gas flow rate, and the effects of the use or non-use of catalysts, and they also investigated the field emission properties of these single-crystalline AlN nanostructures, the results showed that the as-grown AlN nanostructures had a low turn-on field and threshold field of 2.25 and 3.58Vmm-1, respectively. However, the randomly distributed AlN nanostructure is not suitable for the final FED anode due to the screening effect, only the highly ordered and orientated AlN nanoarray is the key for production even emission, high lightening, low loss and addressable FED devices.…”
Section: Introductionmentioning
confidence: 99%
“…1- 6 Here we report on plasma-enabled synthesis of single-crystalline AlN 1D nanorods that combine unique properties specific to bulk AlN and 1D nanomaterials. 3,4 This means that the electrons in the conduction band can escape into the vacuum easily, which can significantly improve the emitting efficiency of AlN-based field emission devices. 7,8 On the other hand, 1D AlN nanostructures with high aspect ratios have very promising applications in field emission devices because of their small and even negative electron affinity.…”
mentioning
confidence: 99%
“…A very wide band gap of ϳ6.2 eV, high thermal conductivity and melting point, low and Si-compatible coefficient of thermal expansion, excellent electrical resistance, low dielectric loss, as well as a strong piezoelectric response renders numerous advanced applications of AlN in light-emitting diodes, surface acoustic wave sensors, reinforcement of functional composites, dielectric layers in optical storage media, etc. 3,4 In comparison with conventional micro-and nanosized AlN particles, single-crystalline 1D AlN nanostructures have better electrical, optical, mechanical properties due to their near perfect crystal structure and high aspect ratios. 3,4 This means that the electrons in the conduction band can escape into the vacuum easily, which can significantly improve the emitting efficiency of AlN-based field emission devices.…”
mentioning
confidence: 99%
See 2 more Smart Citations